Sila-bac, Cold-flo, and sodium hydroxide for forage sorghum silage - K. Bolsen; H. Ilg (Kansas Agricultural Experiment Station Research Reports, 1981)
Inoculant (Sila-bac), non-protein nitrogen (Cold-flo), and alkali (NaOH) silage additives were evaluated with whole-plant forage sorghum silage. All three additives decreased ensiling temperatures. Calves fed Sila-bec or NaOH silages gained 12.0% faster but calves fed Cold-flo silage gained 7.7% slower than those fed control silage. NaOH silage was consumed in the greatest amount; Cold-flo silage, in the least. Calves fed Sila-bec silage were more efficient than calves fed any of the other silages.
Keywords: Cattlemen& #x27; s Day; 1981; Report of progress (Kansas State University. Agricultural Experiment Station); 394; Beef; Sila-bac; Cold-flo; Sodium hydroxide; Sorghum silage